Lymphadenectomy and Sentinel Lymph Node Biopsy in Patients with Endometrial Cancer in Intermediate and High-Intermediate Risk Groups: The Ukrainian Experience - Khoptiana O; Svintsitskyi V; Nespryadko S; Tsip NP; Gogisvanidze T; Dzimistarishvili M; Krasylenko D; Chetverikov MS; Nigutsa IP; Sumtsov D; Dolyk P (International Journal of Women's Health)
Olha Khoptiana,1 Valentyn Svintsitskyi,1 Sergiy Nespryadko,1 Natalia P Tsip,1 Teimuraz Gogisvanidze,2 Mikheil Dzimistarishvili,2 Dmytro Krasylenko,2 Mykhailo Serhiiovych Chetverikov,3 Igor Pavlovych Nigutsa,3,4 Dmytro Sumtsov,4 Pavlo Dolyk5 1Scientific and Clinical Department of the Female Reproductive System Neoplasms, National Cancer Institute, Kyiv, Ukraine; 2Oncogynecological Department, Kyiv Regional Oncology Center, Kyiv, Ukraine; 3Department of Obstetrics and Gynecology, Odesa National Medical University, Odesa, Ukraine; 4Oncogynecological department, Sumy Regional Clinical Oncology Center, Sumy, Ukraine; 5Oncogynecological department, Medical Center “med-Atlant”, Ivano-Frankivsk, UkraineCorrespondence: Olha Khoptiana, National Cancer Institute, Y. Zdanovska Street, Kyiv, 33/43, Ukraine, Tel +380984614138, Email hoptyana.olha@ukr.netPurpose: To analyze the oncological safety of sentinel lymph node biopsy compared to lymphadenectomy. Additionally, we evaluated the postoperative complications of the two methods.Patients and Methods: This retrospective multicenter trial included 118 patients with intermediate and high-intermediate Stage I–II endometrioid endometrial cancer. Patients with non-endometrioid tumors and those with lymphadenopathy detected on computed tomography were excluded. The study group underwent sentinel lymph node biopsy. In contrast, the control group underwent systematic lymphadenectomy up to the renal vessels, the level of the inferior mesenteric artery, or the bifurcation of the iliac vessels. Recurrence-free survival was calculated using the Kaplan–Meier method. Differences were considered statistically significant at p < 0.05 (95% confidence interval).Results: Patients were recruited from 2017 to March 2024. In the control group, six (5.9%) patients experienced disease recurrence and five (4.2%) died. Overall, two (1.7%) patients from both groups died from causes unrelated to recurrence. Recurrence-free survival did not significantly differ between those who underwent sentinel lymph node biopsy (96.3%, SE ± 0.036) and those who underwent lymphadenectomy (89.4%, SE ± 0.045) over 3 years from the date of surgery to the time of the first recurrence (p = 0.608). Eighteen postoperative complications were identified: 11 (9.3%) patients experienced complications within 30 days of follow-up, and 7 (5.9%) within 90 days.Conclusion: Sentinel lymph node biopsy may serve as an alternative to systemic lymphadenectomy for surgical staging without compromising recurrence-free survival.Keywords: sentinel lymph node biopsy, lymphadenectomy, endometrial cancer